A transformerless active voltage quality regulator with the novel three‐leg circuit. Issue 11 (11th June 2021) - Wang, Sen; Pei, Yunqing; Rong, Weiqing; Xiao, Guochun; Huang, Jingjing; Zhang, Jialei
Abstract: Voltage sags and momentary interruptions of power are the most severe voltage disturbances. Here, a tansformerless active voltage quality regulator with the novel three‐leg circuit is proposed to mitigate long duration and deep voltage sags. The shunt rectifier and series inverter of this novel three‐leg circuit are all full‐bridge structures, so it has lower DC bus voltage and smaller filter parameters than the conventional half‐bridge topologies. The totem‐pole bridgeless boost circuit is formed among the three bridge arms and the DC bus voltage will be charged to exceed the peak value of the supply voltage. It can compensate for deep voltage sags (that may be more than 50% of the nominal voltage). Compared to the conventional transformerless series‐connected topology, the proposed topology has the merits of higher efficiency, smaller volume and lower cost. The validity and feasibility of the proposed topology are verified by theoretical analysis, simulation and experiment.